PENYULUHAN DAN PELATIHAN PEMANFAATAN LIMBAH PISANG SEBAGAI BAHAN BAKU KERUPUK - Ratna Mustika Wardhani; Indah Rekyani Puspitawati (Universitas Merdeka Madiun, 2022)
Abstract– Banana fruit is a fruit that has many benefits, ranging from leaves, banana midrib, banana flowers and fruit, including banana peels, because in addition to the fruit which contains many vitamins, banana peel also has a fairly high nutritional and serotonin content. So far banana peels, which are often considered worthless, can also be used to absorb heavy metals, meaning they can purify water. From the benefits of banana peel above, banana peel can be used as a basic food ingredient. Meanwhile, on this occasion the banana peel will be used as the basic ingredient for crackers. The purpose of this activity is to increase the independence of rural community business institutions and to improve the knowledge and skills of women farming communities, especially the